The Fundamental Determinants of the Terms of Trade Reconsidered: Long-Run and Long-Period Equilibrium - Darity, William (American Economic Review, 1990)
Ronald Findlay's analysis of the long-run equilibrium (uniform international growth rates) determinants of the terms of trade, in the context of North-South models of trade and growth, is reconsidered when the North is a Keynesian and a Kaleckian economy. Also examined are the determinants of the terms of trade in long-period equilibrium (uniform profit rates), so that the consequences of capital mobility are accounted for. Two surprising results are noted: first, the long-run terms of trade when the North is a Kaleckian economy will be independent of the North's markup and, second, in the long-period it is theoretically possible for the North to raise its markup but experience a deterioration in its own terms of trade.